SOCIO-ECONOMIC IMPACT OF NGEBUM BEACH TOURISM DEVELOPMENT FOR MOROREJO VILLAGE COMMUNITY - Audinta Mega Ayu Christa; Joko Mariyono; Dian Ayunita Nugraheni Nurmala Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Tourism in Kendal Regency, especially Ngebum Beach in Mororejo Village, has become an important sector in the local economy. Management that was initially community-based by Paguyuban, then shifted to the Village-Owned Enterprise (BUMDes), showed a significant impact on the socio-economy of the surrounding community. This study aims to analyze the social and economic impacts of tourism development in Ngebum Beach. A qualitative approach with a case study method was used to explore the changes that have occurred in the economic and social structure of the Mororejo Village community since tourism management began. The results of the study show that the Ngebum Beach tourism sector has created new jobs, increased household income, and strengthened social solidarity through cultural and spiritual activities. However, there are challenges in the inequality of distribution of economic benefits and changes in local cultural values ​​that need to be managed wisely. Management strategies that involve all parties, including the community, BUMDes, and the government, as well as the use of technology in tourism promotion, can accelerate sustainable tourism development. Thus, the development of Ngebum Beach has the potential to support the achievement of sustainable development goals (SDGs).